(3GdYbjOI GdfSajIs - (3GdfSaj,J (B537 (3g` s ((3ESeGYjd Hf MSf GdQhei s)
(3ChdgG (B:s
(3bGd Cgd GdMb MbGFb GdCTjGA KGHJg hGdYde HgG s
(3BNQgG (B:s
(3hWdhY GdTeS ef eZQHgG agh Mb hGdeLJgO bO jNWF hjUjH hQSd CaVd ef QSd GdedGFcI ef YGeI GdedGFcI Ke GdcJGH HYhf Gddg GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg aGFOI ddTjN GdLhgQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B305s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs